Designing an Adaptive UI/UX Application to Support Self-Directed - Syaika, Ghini Righida; Wardhani, Dyah Febria (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
In the digital era, the effectiveness of self-directed learning poses a challenge for many individuals, particularly in managing time optimally. This study aims to design a digital time-tracking application with a UI/UX design focused on enhancing the effectiveness of self-directed learning. The application is expected to help users allocate study time more systematically and improve their productivity. The research employs a User-Centered Design (UCD) approach, which involves user needs analysis, wireframe design, and application prototyping. The design process is carried out through literature reviews, potential user surveys, and UI/UX design analysis based on accessibility, convenience, and ease of use principles. The study results indicate that the application design features key functionalities such as study time tracking, learning habit analysis, and reminders tailored to users' needs. Based on prototype evaluation, the applied design is considered intuitive and effective in helping users manage their study time more efficiently. In conclusion, the design of this digital time-tracking application demonstrates potential in improving self-directed learning effectiveness through an optimized UI/UX approach. Although this study focuses only on the design stage without actual implementation, the results can serve as a foundation for further development in creating a fully functional application.
Keywords: Application Design; UI/UX; Learning Effectiveness; Self-Directed Learning